PENGARUH UPAH DAN INSENTIF TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. TIRTA BUMI RAYA PALEMBANG - M Maliah; Deki Kurniawan (JURNAL KOMPETITIF, 2020)
This research is a study of "The Effect of Wages and Incentives on Employee Productivity at PT. Tirta Bumi Raya Palembang ". The dependent variable in this study is Work Productivity and the independent variables are Wages and Incentives. The data used in this study are primary data obtained from data processing and questionnaires. The population in this study amounted to 50 employees, the method of determining the sample using the census method that is all the population into the study sample. Data collection techniques using questionnaires that have been tested first are tested using validity test and reliability test. Data analysis techniques used are multiple linear regression analysis, coefficient of determination, t test and F test. The results of this study, prove that partially and simultaneously wages partially have a significant effect on work productivity. Then partial incentives do not significantly influence work productivity. While simultaneously wages and incentives simultaneously have a significant effect on employee work productivity.  Keywords: Wages, Incentives and Work Productivity